The complete chloroplast genome sequence of Salix viminalis (Salicaceae) - Hua-Lei Hu; Hao Lin; Xu-Hui Chen; Yan-Qun Liu; Li Qin (Mitochondrial DNA. Part B. Resources, 2019)
Here, the complete chloroplast (cp) genome of Salix viminalis was reported. The genome is 155,531 bp long, with a GC content of 36.71%, and contains four sub-regions: 84,395 bp of large single copy (LSC) and 16,218 bp of small single copy (SSC) regions, separated by 27,459 bp of inverted repeat (IR) regions. A total of 129 genes were annotated, including 83 protein-coding genes, 38 tRNA genes, and 8 rRNA genes. The Phylogenetic analyses based on the whole cp genome sequence placed S. viminalis into a clade containing Salix rehderiana, Salix taoensis, Salix koriyanagi, and Salix suchowensis. This is the first complete cp genome for S. viminalis that would be useful for phylogenetic and population genetic studies of this species.